Sleep tight - Kine, Jamie; Marshall, Tim; Poston, Mike; Tice, Hnnah (Tennessee, USA CURB records, 2008)
The perfect blend of instrumental music and gentle vocal ballads, this CD is ideal for any baby's beditime routine. Creating a peaceful and comforting atmosphere for little ears, will calm and soothe your sweet one to sleep every night
Oh mio babbino caro -- rock-a-bye Baby -- Toyland -- All night all day -- scarborough fair -- Polish lullaby -- sleep baby sleep -- Ghonandoah -- All through the night -- Bist du bei mir -- Golden cradle -- now the day is over
"12 lullaby favorites for your bee-autiful baby"
sound recording
12
Keywords: Concerts; Harmony; Music; Sound recordings